2020
DOI: 10.3390/brainsci10020078
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Neuropsychiatric Symptoms over Time in an Incident Parkinson’s Disease Cohort (ICICLE-PD)

Abstract: Background: Cross-sectional studies have identified that the prevalence of neuropsychiatric symptoms (NPS) in Parkinson’s disease (PD) ranges from 70–89%. However, there are few longitudinal studies determining the impact of NPS on quality of life (QoL) in PD patients and their caregivers. We seek to determine the progression of NPS in early PD. Methods: Newly diagnosed idiopathic PD cases (n = 212) and age-matched controls (n = 99) were recruited into a longitudinal study. NPS were assessed using the Neuropsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Lower income, worse mood in the care partner as measured by the short form of the Profile of Mood States of the care partner, and increased motor severity of the person with PD have been identified as predictors of poorer care partner quality of life in a follow‐up of 12 months, while economic pressure, relationship satisfaction, and social support were not identified as such 10,15 . Physical activity of the person with PD at baseline was found to be associated with less future care partner burden at the timepoint of 3 years 13 …”
Section: Resultsmentioning
confidence: 99%
“…Lower income, worse mood in the care partner as measured by the short form of the Profile of Mood States of the care partner, and increased motor severity of the person with PD have been identified as predictors of poorer care partner quality of life in a follow‐up of 12 months, while economic pressure, relationship satisfaction, and social support were not identified as such 10,15 . Physical activity of the person with PD at baseline was found to be associated with less future care partner burden at the timepoint of 3 years 13 …”
Section: Resultsmentioning
confidence: 99%
“…Conversely, many epidemiological studies have suggested that MDD can increase the likelihood of developing PD in later life [7, 8]. This highlights MDD as a mental health concern that is not only debilitating through its influence on mood but also in its potential to predispose physical impairments in the form of parkinsonism.…”
Section: Introductionmentioning
confidence: 99%
“…These neuropsychiatric symptoms even contribute more to the caregiver burden of PD partners than motor impairment [ 2 , 5 , 12 ]. Caregiver distress increases along with worsening neuropsychiatric symptoms and lower quality of life of PD patients [ 13 ]. In a cross-sectional observational study of 89 PD patients and 84 caregivers, neuropsychiatric symptoms, such as mood changes and apathy but also MDS-Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) II, caregiving hours per day and caregivers’ Beck Depression Inventory (BDI), had the most impact on CB [ 14 ].…”
Section: Preoperative Caregiver Burden—dbs Yes or No?mentioning
confidence: 99%